1986
DOI: 10.1136/oem.43.5.327
|View full text |Cite
|
Sign up to set email alerts
|

Branchial challenge of normal subjects with the endotoxin of Enterobacter agglomerans isolated from cotton dust.

Abstract: Endotoxin produced by a culture of Enterobacter agglomerans isolated from cotton dust was inhaled by 12 normal subjects. No significant airway constriction was obtained in doses equivalent to those experienced in a workshift in a dusty mill. There was a statistically significant difference between this result and the bronchoconstriction that had occurred after flax dust inhalation in the same subjects. It is suggested that Enterobacter agglomerans endotoxin is not the causative agent of the acute bronchoconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The threshold doses causing symptoms, standardized by the Limulus test, were equal to 30 µg of LPS-PW or 300 µg of CE-A. The results of this research explained the negative results obtained earlier by Jamison and Lowry [99] from the University of Belfast in Northern Ireland, who did not observe a drop in spirometric values and occurrence of symptoms in human volunteers exposed to P. agglomerans LPS-PW in the doses of 5 μg and 12 μg, which were simply too low to evoke any reaction (except for a significant drop in DLCO after exposure to 12 μg of LPS). This assessment was supported later by Thorn [100] who assumed that inhalation of 30-40 μg LPS seems to be a threshold level for inducing clinical symptoms and lung function changes in healthy human subjects.…”
Section: Dust-borne Endotoxins and Allergens Of Pantoea Agglomerans -supporting
confidence: 74%
See 1 more Smart Citation
“…The threshold doses causing symptoms, standardized by the Limulus test, were equal to 30 µg of LPS-PW or 300 µg of CE-A. The results of this research explained the negative results obtained earlier by Jamison and Lowry [99] from the University of Belfast in Northern Ireland, who did not observe a drop in spirometric values and occurrence of symptoms in human volunteers exposed to P. agglomerans LPS-PW in the doses of 5 μg and 12 μg, which were simply too low to evoke any reaction (except for a significant drop in DLCO after exposure to 12 μg of LPS). This assessment was supported later by Thorn [100] who assumed that inhalation of 30-40 μg LPS seems to be a threshold level for inducing clinical symptoms and lung function changes in healthy human subjects.…”
Section: Dust-borne Endotoxins and Allergens Of Pantoea Agglomerans -supporting
confidence: 74%
“…This assessment was supported later by Thorn [100] who assumed that inhalation of 30-40 μg LPS seems to be a threshold level for inducing clinical symptoms and lung function changes in healthy human subjects. The British authors [99] used purified LPS (LPS-PW), which was less appropriate for the study of exposure effects than CE-A. In the conclusion of their work, Rylander et al [28] expressed an opinion that their results support the hypothesis that bacterial endotoxins cause mill fever, grain handler's fever and humidifier fever.…”
Section: Dust-borne Endotoxins and Allergens Of Pantoea Agglomerans -mentioning
confidence: 99%
“…Saline solution has generally been used as the solvent rather than distilled water since the latter may cause bronchoconstriction [36]. Most investigators have used LPS from Escherichia coli [19, 23-29, 32, 34], although some have obtained extracts of LPS from Enterobacter agglomerans [21,22] and Haemophilus influenzae [20]. To my knowledge, there are no published reports (with human subjects) of a comparison of the responses to endotoxin from different Gram-negative bacteria or the different methods of extraction.…”
Section: Discussionmentioning
confidence: 99%
“…The different doses of LPS used in the studies suggest a threshold level for inducing clinical symptoms after LPS inhalation of approximately 30 -40 mg [22,34], while 12 and 20 mg of inhaled LPS was not found to induce any symptoms [21,29]. Larsson et al [38] showed that symptoms such as fever and malaise were induced in normal subjects using an endotoxin concentration of 0.08 -1.3 mg/m 3 in airborne swine dust, which roughly corresponded to approximately 2.0 to 3.0 mg LPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation